To the memory of Nikolai Markovich Sergienko (Ukrainian Journal of Ophthalmology, 2026)
With deep sorrow we inform that Nikolai Markovich Sergienko, an outstanding scientist, a corresponding member of NAS and NAMS of Ukraine, Dr. of Sc. (Med.), Professor, Honored Worker of Science and Technology, Laureate of the State Prize in Science and Technology, Professor of Ophthalmology Department of Shupyk National Medical Academy of Postgraduate Education, Vice-President of Association of ophthalmology surgeons, and a scientist who is well-known not only in Ukraine but abroad, passed away on June, 29, 2017. He was 83.